2009
DOI: 10.1001/archsurg.2008.503
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Predictors of Mortality and Stoma Formation in Surgical Management of Colonoscopic Perforations

Abstract: Colonoscopic perforations were in a decreasing trend. Patients with predictors of mortality should not be treated conservatively. Other options of large bowel investigations should be considered in high-risk patients when the potential diagnostic yield is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
57
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 29 publications
8
57
1
Order By: Relevance
“…Large series of colonoscopy induced perforations managed surgically reported a morbidity rate of 35% [4,7]. The mortality rate in our study is fairly comparable to other reports which is up to 25% [7,8]. Surgical site infection is the most common complication, while cardiopulmonary complications and multiple organ failure are the leading causes of death [7,24].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Large series of colonoscopy induced perforations managed surgically reported a morbidity rate of 35% [4,7]. The mortality rate in our study is fairly comparable to other reports which is up to 25% [7,8]. Surgical site infection is the most common complication, while cardiopulmonary complications and multiple organ failure are the leading causes of death [7,24].…”
Section: Discussionsupporting
confidence: 81%
“…Our study demonstrated the same results, but we didn't find statistical significant relationship between time to surgery and postoperative complications. Several other factors are also known to influence outcome, namely, advanced age of patients, severe comorbidities, a large perforation site, poor bowel preparation, corticosteroid use, anticoagulant or antiplatelet therapy [7,8,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perforations may be pneumatic due to excessive distension of the intestinal wall from high-pressure insufflations or mechanic from the pressure exerted by the gastroenterologist [3]. With regards to the time of diagnosis, perforations produced from diagnostic colonoscopy (due to the mechanical pressure) are larger and are detected promptly since patients are admitted earlier, while those occurring from therapeutic colonoscopy are diagnosed late and are smaller in size [4]. Sigmoid colon is more often affected [5].…”
Section: Discussionmentioning
confidence: 99%
“…This was associated with 13% mor-tality and 53% morbidity [3]. Recently, two extensive reviews of the outcomes following CP by Iqbal [4] and Teoh [5] showed a mortality rate of 7-26% and a morbidity rate of 37-49%, together with a 38% rate of intestinal stoma formation.…”
Section: Introductionmentioning
confidence: 99%